The ratio of soluble fms–like tyrosine kinase 1 to placental growth factor predicts time to delivery and mode of birth in patients with suspected preeclampsia- a secondary analysis of the INSPIRE trial - Palma Dos Reis, CR; O’Sullivan, J; Ohuma, EO; James, T; Papageorghiou, AT; Vatish, M; Cerdeira, AS (Elsevier, 2024)
Background: The ratio of soluble fms–like tyrosine kinase 1 to placental growth factor (sFLT1/PLGF) is a useful biomarker for preeclampsia. Since it is a measure of placental dysfunction, it could also be a predictor of clinical deterioration and fetal tolerance to intrapartum stress. Objectives: We tested the hypothesis that sFLT1/PLGF ratio predicts time to delivery. Secondary objectives were to examine associations between the sFLT1/PLGF ratio and mode of birth, fetal distress, need for labor induction and birthweight z-score. Study design: Secondary analysis of the INSPIRE trial, a randomized interventional study on prediction of preeclampsia/eclampsia in which women with suspected preeclampsia were recruited and their blood sFLT1/PLGF ratio was assessed. We stratified participants into three groups according to the ratio result: category 1 (sFLT1/PLGF≤38); category 2 (sFLT1/PLGF>38 and <85); and category 3 (sFLT1/PLGF≥85). We modelled time from sFLT1/PLGF determination to delivery using Kaplan-Meier curves and compared the three ratio categories adjusting for gestational age at sFLT1/PLGF determination and trial arm with Cox Regression. The association between ratio category and mode of delivery, induction of labour and fetal distress was assessed using a multivariable logistic regression adjusting for gestational age at sampling and trial arm. The association between birthweight z-score and sFLT1/PLGF ratio was evaluated using multiple linear regression. Subgroup analysis was conducted in women with no preeclampsia and spontaneous onset of labor; women with preeclampsia; and participants in the non-reveal arm. Results: Higher ratio categories were associated with a shorter latency from sFLT1/PLGF determination to delivery (37 vs 13 vs 10 days for ratios categories 1-3 respectively), hazards ratio for category 3 ratio of 5.64 (95%CI 4.06-7.84, p<0.001). A sFLT/PlGF ratio≥85 had specificity of 92.7%(95%CI 89.0-95.1%) and sensitivity of 54.72% (95% CI, 41.3-69.5) for prediction of preeclampsia indicated delivery within 2 weeks. A ratio category 3 was also associated with decreased odds of spontaneous vaginal delivery (OR 0.47, 95%CI 0.25-0.89); an almost six fold increased risk of emergency cesarean section (OR 5.89, 95%CI 3.05-11.21); and a three-fold increased risk for intrapartum fetal distress requiring operative delivery or cesarean section (OR 3.04, 95%CI 1.53-6.05) when compared to patients with ratios≤38. Higher ratio categories were also associated with higher odds of induction of labor when compared to ratios category 1 (category 2, OR 2.20, 95%CI 1.02-4.76; category 3, OR 6.0, 95%CI 2.01-17.93); and lower median birthweight z-score. Within subgroups of women a)without preeclampsia and with spontaneous onset of labor and b)women with preeclampsia, the log ratio was significantly higher in patients requiring intervention for fetal distress or failure to progress compared to those who delivered vaginaly without intervention. In the subset of women with no preeclampsia and spontaneous onset of labour, those who required intervention for fetal distress or failure to progress had a significantly higher log ratio than those who delivered vaginaly without needing intervention. Conclusion: The sFLT1/PLGF ratio might be helpful in risk-stratification of patients who present with suspected preeclampsia regarding clinical deterioration, intrapartum fetal distress and mode of birth (including the need for intervention in labour).